Impact of providing information about the fat content, primal source, price, and labeling terms on consumer sensory evaluation of ground beef from the same source - Harr, Keayla (Kansas State University, 2021)
The objective of these studies was to evaluate the effect of supplying information about the fat content, primal source, price, and branding information prior to consumers sensory evaluation of ground beef from an identical source. Ground beef (80% lean / 20% fat) chubs (n = 30) were procured from the same production lot and day and manufactured into 151.2 g patties. Each chub was randomly assigned to two panels for one of the four different treatment categories: fat content, primal source, price, or branding. Samples designated for fat panels were labeled as: 90% lean / 10% fat (90/10), 80% lean / 20% fat (80/20), 73% lean / 27% fat (73/27), lean, and extra lean. Primal source samples were labeled as: ground chuck, ground round, ground sirloin, and store ground. Samples designated for price panels were labeled with one of five different price points: ultra-high, high, medium, low, and ultra-low. Labeling terms utilized and randomly labeled for branding panels: all natural, animal raised without added antibiotics (WA), animal raised without added hormones (WH), fresh never frozen (FNF), grass-fed, locally sourced, premium quality, and USDA organic (ORG). An additional sample for each panel had no information provided (NONE). Samples were fed to consumers (N = 420; 105 / panel type) who evaluated each sample on 0-to-100-point line scales for tenderness, juiciness, flavor, texture, overall liking, and purchasing intent, and evaluated each trait as either acceptable or unacceptable. Ground beef labeled as 90/10, 80/20, and 73/27 had a large increase (P < 0.05) in consumer ratings for tenderness, flavor, and overall liking when the treatment was disclosed to consumers. When consumers were informed of the price of the product, large increases (P < 0.05) were observed for all palatability traits on samples that were priced at the ultra-high, high, medium, and ultra-low-price points. Additionally, when the primal blend type was disclosed, there was a large increase (P < 0.05) for all palatability traits evaluated for all four primal blend treatments. Informing consumers about the price and primal blend increased (P < 0.05) the purchasing intent ratings for all price and primal blend treatments. For flavor liking, there was a larger increase (P < 0.05) in ratings for samples labeled as grass-fed in comparison to WA, WH, and premium quality labeled samples. There was a large increase (P < 0.05) in the consumer ratings for overall liking when product was labeled as all natural, WA, WH, FNF, locally sourced, premium quality, and ORG. Additionally, there was a larger decrease (P < 0.05) in the percentage of samples rated as acceptable overall when labeled as WA in comparison to all other treatments. Ultimately, adding production claims that consumers are familiar with gives a “brand lift” to ground beef. Furthermore, consumers are impacted both negatively and positively impacted in their eating experience when they are aware of the fat content, primal source, and price of ground beef.
Keywords: Consumer; Ground beef; Branding; Palatability; Labeling